Fraud Auditing and Forensic Accounting: New Tools and Techniques. - Albrecht, W. Steve; Boatsman, James R. (The Accounting Review, 1996)
Abstract Reviews the book `Fraud Auditing and Forensic Accounting,' by G. Jack Bologna and Robert J. Lindquist.